Avaliação do estresse oxidativo e lesão muscular no exercício resistido de alta intensidade em animais tratados com Bowdichia virgilioides - Santos, Jymmys Lopes dos (2014)
Despite being considered as a safe form of exercise, carrying out high-intensity resistance exercise (RE) can cause periods of ischemia-reperfusion and can consequently lead to an increase in free radicals (FR). The use of natural antioxidants can reduce oxidative damage caused by high-intensity RE. The aim of this study was to investigate the antioxidant potential in vitro and the protective effect exerted by the hydroethanolic extract (HEE) of Bowdichia virgilioides (BV) on muscular damage and oxidative stress in rats subjected to high-intensity RE. Methods: Male Wistar rats with 200 250 grams of body weight were divided into four groups: 1) Control group (CG), vehicle-treated (Tween 80, oral administration, P.O.) and electrostimulation; 2) Trained group (TG), vehicle-treated (Tween 80, 3% P.O.) and resistance training; 3) BV untrained group (BVG), treated with HEE of BV (200 mg kg-1, P.O); 4) Trained BV group (TBVG), treated with HEE of BV (200 mg kg-1, P.O.). Lipid peroxidation in plasma and tissue was diminished at 55.68% (p<0.0001), and 66.61% (p<0.0012), respectively, from TBVG comparing to TG. In addition, oxidative stress was diminished at 62.83% (p<0.0005), and 54.97% (p<0.0197) in plasma and skeletal muscle, respectively, from TBVG comparing to TG. HEE of BV was capable of reducing some oxidative stress markers caused by high-intensity RT, and reduced the content of some marker enzymes of tissue damage.